PENGARUH KONSUMSI BAYAM HIJAU (Amaranthus sp) TERHADAP KADAR HB PADA IBU HAMIL DENGAN ANEMIA RINGAN DI WILAYAH KERJA PUSKESMAS KUNDUR BARAT - Herlin, Lidia; Aryaneta, Yenni (Universitas Batam, 2019)
The Kundur Barat Health Centre apparently was noticed due to its high anemia incidence rate in 2017 which happened to 29.1% pregant women, this number is the second highest rate of anemia in Karimun occurred on mothers with hemoglobin (Hb) level of 9 g/dl at their first visit. The study aims to determine the impact of green spinach (Amaranthus sp) consumption on the average escalation of Hb levels on pregnant mothers with light anemia syndrome at Kundur Barat Health Centre of Karimun conducted from March to July 2018. Anemia in pregnancy happens as a condition of the mothers with hemoglobin below 11g/dl. The most common cause of anemia in pregnancy is iron deficiency which possibly triggers pregnant women to get a miscarriage, premature birth, bleeding before and during childbirth, and in severe anemia, it can cause maternal and infant death. One alternative to meet iron requirements is to routinely consume food with high iron (Fe), for instance spinach. This research is a quantitative research with quasy experiment of one group pretest and posttest research design to 34 respondents. The result shows the pretest mean score = 9.65 and posttest mean score = 12.48. On the other hand, the Paired-Sample T-Test confirms a significant difference on before and after consumption of green spinach (Amaranthus sp) of mean score = 2.83 with p value <0.0000 (p > 0.05).Â Lastly, it is hoped that pregnant women to consume green spinach (Amarantus sp) as an alternative to increase their Hb levels.